Komodifikasi Konten di Radio Berita Lokal: (Studi Kasus Intrinsik Radio PRFM 107.5 News Channel Bandung) - Nadya Yasmine Khaerunnisa; Achmad Abdul Basith; Rinda Aunillah Sirait (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humani..., 2026)
Radio PRFM 107.5 News Channel Bandung has established its reputation as a citizen journalismbased local news radio through the slogan "Andalah Reporter Kami" (You Are Our Reporter). However, economic imperatives have steadily blurred the boundary between journalistic function and business logic, raising concerns about editorial independence in local broadcast media. This study aims to analyze content commodification practices at PRFM across both production and multiplatform distribution stages. Employing Vincent Mosco's (2009) political economy of communication theory, a qualitative approach with Robert E. Stake's intrinsic case study design was adopted. Data were collected through nonparticipant observation, indepth interviews, and literature study, subsequently validated through source triangulation. Findings reveal that content commodification operates systematically across two stages. During production, commodification manifests through marketdriven issue selection, sensational headline construction, and the strategic management of talkshow programs as advertiser recruitment instruments. During distribution, multiplatform content repurposing practices encompassing rhetoric of recombination, augmentation, and reversioning enable a single piece of information to be capitalized across multiple platforms simultaneously. Furthermore, PRFM's financial dependence on government advertisers, accounting for 85% of total advertising revenue, demonstrably erodes editorial independence and shifts the station's function from press watchdog to a media outlet vulnerable to external intervention. These findings imply that economic pressures in local media ecosystems require stronger institutional safeguards to protect journalistic integrity.